Torque variations of ball bearings based on dynamic model with geometrical imperfections and operating conditions. (May 2019) - Zhang, Xi; Xu, Hua; Chang, Wei; Xi, Hui; Xing, Yu; Pei, Shiyuan; Wang, Fengcai
Abstract: A friction torque model of ball bearings with geometrical imperfections is proposed, integrating developed models of friction, raceway waviness, and multi-body dynamics. Torque variations consisting of average and fluctuation values for angular contact ball bearings due to waviness including linear, nonlinear and multi-orders situation are analyzed in time and frequency domains. The influences of waviness amplitude, load and speed are evaluated. Additionally, the correlation between axial displacement and torque fluctuation of ball bearings is discussed, and their spectrum similarity under pure axial load and the relative low-frequency amplitude enhancement of the torque spectrum under combined load are observed. Finally, a torque experiment is carried out on a bearing test apparatus, and the effectiveness of the present model is verified. Highlights: The integrated friction torque model of ball bearings with geometrical imperfections was developed. The non-linear waviness not only influenced the torque fluctuation, but also affected the mean torque. The obvious torque fluctuation at the radial excitation frequency required the existence of radial load. There was similarity between the spectrum of friction torque and axial displacement under axial load. There was relative low-frequency amplitude enhancement of the torque spectrum under combined load.